Information frictions, belief updating and internal migration: Evidence from Ghana and Uganda - Sarah Frohnweiler; Bernd Beber; Cara Ebert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Information frictions about the benefits of migration can lead to inefficient migration choices. We study the effects of a randomly assigned information treatment about regional income differentials in Ghana and Uganda to learn about participants' belief updating and subsequent changes in migration intentions and destination preferences. Participants react to the provided information by correcting their destination preferences towards regions with higher incomes, whereas their intent to migrate changes less. Participants' belief updating follows an asymmetric process restricted to individuals who initially underestimated regional differentials. The results suggest that income differentials matter for where to and less whether to migrate. – – Informationsdefizite über die Vorteile von Migration können zu ineffizienten Migrationsentscheidungen führen. Wir untersuchen wie sich zufällig bereitgestellte Information über regionale Einkommensunterschiede in Ghana und Uganda auf die Migrationsabsichten und Zielpräferenzen von Menschen auswirkt. Studienteilnehmende reagieren auf die bereitgestellten Informationen, indem sie ihre Zielpräferenzen zugunsten von Regionen mit höherem Einkommen korrigieren. Migrationsabsichten ändern sich weniger stark. Die Aktualisierung der Zielpräferenzen folgt einem asymmetrischen Prozess und beschränkt sich auf Personen, die die regionalen Unterschiede anfänglich unterschätzen. Die Ergebnisse deuten darauf hin, dass regionale Einkommensunterschiede eine besonders wichtige Rolle spielen für die Entscheidung wohin man migriert und weniger ob man migriert.
Keywords: J31; J68; O15; 330; Income differentials; migration decision; belief updating